North American crayfish: A quest for the biggest catch - Caitlin C. Bloomer; Susan B. Adams; Zanethia C. Barnett; Zackary A. Graham; Emmy M. Delekta; David M. Hayes; Zachary J. Loughman; Hugh MacIntosh; M. Worth Pugh; Karen Reed; Nathaniel F. Shoobs; Christopher A. Taylor; et al. (Ecology, 2026)

Nonlinear thinking in ecology and evolution: applying the threshold elemental ratio across levels of ecological organization - Benjamin B. Tumolo; Carly R. Olson; Erin I. Larson; Halvor M. Halvorson; Catherine E. Wagner; Amy C. Krist; Felicia S. Osburn; Eric K. Moody; Linnea A. Rock; Uchechukwu V. C. Ogbenna; Eli N. Wess; Briante Najev; et al. (Oecologia, 2026)
Nonlinear dynamics govern ecological processes; thus, understanding thresholds is important for measuring and forecasting the effects of climate change and management of natural resources. However, identifying whether and how such thresholds transfer across ecological levels of organization remains challenging. We argue for a broadening of a foundational organismal concept from ecological stoichiometry theory, the threshold elemental ratio (TER), to study how nonlinear dynamics driven by shifts in limitation operate in evolutionary and ecological processes from organisms to ecosystems. Traditionally, TERs are used to describe the elemental ratio at which the limitation of organismal growth shifts from one element to another. Building on this definition, we make a case for broadening the TER beyond organisms to include populations, clades, communities, and ecosystems. We discuss how TERs may be detected and translated across different ecological levels and evolutionary processes through simulation modeling, literature review, and synthesis of empirical examples from diverse systems and scales including: cyanotoxin production in lakes, alder–salmon dynamics, and the Cambrian explosion. Collectively, we argue that TERs are likely widespread and consequential across levels of ecological organization and that such thresholds manifest from a diversity of mechanisms. Thus, applying the TER concept across ecological levels of organization holds promise for advancing our understanding of nonlinear dynamics from the micro-evolutionary to the macro-ecological.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Sex differences in neuroendocrine, sympathetic nervous system, and affect responses to acute stress in cannabis users - Eric R. Larson; Alexandra B. Moussa-Tooks; Rachel L. Tullar; Amanda R. Bolbecker; Brian F. O’Donnell; William P. Hetrick; Krista M. Wisner (Psychopharmacology, 2023)

Association of cerebral microvascular dysfunction and white matter injury in Alzheimer’s disease - Zsolt Bagi; Christopher D. Kroenke; Katie Anne Fopiano; Yanna Tian; Jessica A. Filosa; Larry S. Sherman; Eric B. Larson; C. Dirk Keene; Kiera Degener O’Brien; Philip A. Adeniyi; Stephen A. Back (GeroScience, 2022)

The FamilyTalk randomized controlled trial: patient-reported outcomes in clinical genetic sequencing for colorectal cancer - Sukh Makhnoon; Deborah J. Bowen; Brian H. Shirts; Stephanie M. Fullerton; Eric B. Larson; James D. Ralston; Kathleen A. Leppig; David R. Crosslin; David Veenstra; Gail P. Jarvik (Cancer Causes & Control, 2021)

“It would be so much easier”: health system-led genetic risk notification—feasibility and acceptability of cascade screening in an integrated system - Nora B. Henrikson; Paula R. Blasi; Stephanie M. Fullerton; Jane Grafton; Kathleen A. Leppig; Gail P. Jarvik; Eric B. Larson (Journal of Community Genetics, 2019)

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

A genome- and phenome-wide association study to identify genetic variants influencing platelet count and volume and their pleiotropic effects - Khader Shameer; Joshua C. Denny; Keyue Ding; Hayan Jouni; David R. Crosslin; Mariza de Andrade; Christopher G. Chute; Peggy Peissig; Jennifer A. Pacheco; Rongling Li; Lisa Bastarache; Abel N. Kho; et al. (Human Genetics, 2014)

Genetic variants associated with the white blood cell count in 13,923 subjects in the eMERGE Network - David R. Crosslin; Andrew McDavid; Noah Weston; Sarah C. Nelson; Xiuwen Zheng; Eugene Hart; Mariza de Andrade; Iftikhar J. Kullo; Catherine A. McCarty; Kimberly F. Doheny; Elizabeth Pugh; Abel Kho; et al. (Human Genetics, 2012)

The human FE65 gene: genomic structure and an intronic biallelic polymorphism associated with sporadic dementia of the Alzheimer type - Q. Hu; Walter A. Kukull; Steven L. Bressler; Matthew D. Gray; Judith A. Cam; Eric B. Larson; George M. Martin; Samir S. Deeb (Human Genetics, 1998)